An Evaluation of a Nutraceutical with Berberine, Curcumin, Inositol, Banaba and Chromium Picolinate in Patients with Fasting Dysglycemia - Derosa, Giuseppe (Diabetes Metab Syndr Obes, 2020)
AIM: To evaluate if a nutraceutical containing Berberine, Curcumin, Inositol, Banaba, and Chromium Picolinate (Reglicem(®)), can ameliorate glycemic status in patients with dysglycemia. METHODS: We enrolled 148 patients with impaired fasting plasma glucose or impaired glucose tolerance, not taking any hypoglycemic compounds. Patients were randomized to take nutraceutical or placebo for 3 months, in a randomized, double-blind, placebo-controlled design. Both nutraceutical and placebo were self-administered once a day, 1 tablet during the breakfast. RESULTS: A reduction of fasting and post-prandial plasma glucose was observed with the nutraceutical combination (p < 0.05 vs baseline and p < 0.05 vs placebo, respectively). Furthermore, a decrease of glycated hemoglobin, and fasting plasma insulin was observed with the nutraceutical combination (p < 0.05 vs baseline and p < 0.05 vs placebo, respectively). Then, there was a reduction of homeostasis model assessment index with the nutraceutical combination (p < 0.05 vs baseline and p < 0.05 vs placebo). M value was higher (p < 0.05 vs baseline and p < 0.05 vs placebo) in the nutraceutical combination group at the end of the treatment. We observed a reduction of total cholesterol (TC) (p < 0.05 vs baseline) and triglycerides (Tg) (p < 0.05 vs baseline and p < 0.05 vs placebo) with the nutraceutical combination, respectively. Finally, high sensitivity C-reactive protein was reduced after 3 months with nutraceutical combination therapy (p < 0.05 vs baseline and p < 0.05 vs placebo, respectively). CONCLUSION: A nutraceutical containing Berberine, Curcumin, Inositol, Banaba, and Chromium Picolinate can be helpful in improving glyco-metabolic compensation, TC and Tg value, and in reducing inflammatory status in patients with dysglycemia.